Security Analysis and The Effect of Codec Changes on Quality of Service of Encrypted Voice Phones on Voice Over IP Freepbx - Asep Saepul Achmad; Muhammad Nursalman; Rizky Rachman J. (Universitas Pendidikan Indonesia, 2023)
VoIP is one of the technologies as communication with audio and video media online. The server secures voice phone data on VoIP supporting VoIP phone data encryption. In addition to security, in order to improve sound quality FreePBX also uses the latest codecs such as Alaw, Ulaw, G722, G729. The purpose of this study was to display the results of VoIP voice phone security testing on FreePBX Server, analyze the Quality of Service of voice codecs on VoIP phones, and compare encrypted and unencrypted VoIP voice phones. The Quality-of-Service criteria of voice telephony consist of packet loss, jitter, and delay or delta. Then, test VoIP security using the Man in The Middle Attack (ARP Poisioning) attack method on the Cain and Abel application. Next, analyze the comparison between encrypted and unencrypted phones using SoftPhone SIPSoercery. Test results for QoS of encrypted VoIP phones with different audio codecs are very good and this assessment is based on the TIPHON QoS standard. The best delta value is found in the Ulaw codec and the best jitter value is found in the Alaw codec. After VoIP phones are attacked with ARP Poisoning, there is a decrease in QoS quality. For all codecs tested, the delta value decreased from 9.34% to 104.12%, the jitter value decreased from 235.49% to 767.97%, and the packet loss value decreased from 5.56% to 181.82%.